Nanoemulsion Adjuvant Augments Retinaldehyde Dehydrogenase Activity in Dendritic Cells via MyD88 Pathway - Farazuddin, Mohammad; Goel, Rishi R.; Kline, Nicholas J.; Landers, Jeffrey J.; O'Konek, Jessica J.; Baker Jr., James R. (Frontiers in Immunology, 2019)
Mucosal surfaces are the primary point of entry for many infectious agents and mucosal immune responses serve as the primary defense to these pathogens. In order to mount an effective mucosal immune response, it is important to induce T cell homing to mucosal surfaces. Conventional vaccine adjuvants induce strong systemic immunity but often fail to produce mucosal immunity. We have developed an oil-in-water nanoemulsion (NE) adjuvant that provides mucosal immunity and efficient protection against mucosal pathogens when administered as part of an intranasal vaccine. In the present study, we demonstrate that intranasal immunization with NE indirectly activates the retinaldehyde dehydrogenase (RALDH) activity in dendritic cells through epithelial cell activity leading to SIgA as well as potent cellular responses and expression of α4β7 and CCR9 gut homing receptors on T cells. Confirming these findings, ex-vivo stimulation of splenocytes from NE nasally immunized animals showed increase in Th1/Th17 cytokines while suppressing Th2 responses. In examining mechanisms underlying this activation NE activated RALDH via MyD88 dependent pathways in DCs but did not activate the retinoic acid receptor directly. These results suggest that RALDH immune activities can be achieved by epithelial activation without direct RAR activation, which has significant implications for understanding mucosal immunity and the design of mucosal vaccines.